A comparison of right posterior sectorectomy with formal right hepatectomy: a dual‐institution study. Issue 10 (22nd July 2013) - Fisher, Sarah B.; Kneuertz, Peter J.; Dodson, Rebecca M.; Patel, Sameer H.; Maithel, Shishir K.; Sarmiento, Juan M.; Russell, Maria C.; Cardona, Kenneth; Choti, Michael A.; Staley, Charles A.; Pawlik, Timothy M.; Kooby, David A.
Abstract: Objectives: Right posterior sectorectomy (RPS) preserves liver volume but typically requires a longer parenchymal transection distance than does right hepatectomy (RH). This study was conducted to define the advantages of one approach over the other. Methods: Databases at two institutions were retrospectively reviewed for all patients submitted to RPS or RH between January 2000 and August 2012. Primary outcomes were perioperative complications and 90‐day mortality. Results: Patients undergoing RPS ( n = 100) and RH ( n = 480), respectively, were similar in demographics, comorbidities, operative indications and Model for End‐stage Liver Disease (MELD) mean scores (7.8 in the RPS group and 7.7 in the RH group; P = 0.49). A comparison of the RPS group with the RH group showed no significant differences in mean estimated blood loss (697 ml versus 713 ml; P = 0.900), rate of transfusions (19.2% versus 17.1%; P = 0.720), margin‐positive resection (9.2% versus 11.6%; P = 0.70), complications (41.8% versus 42.0%; P = 1.000), bile leak (3.0% versus 4.0%; P = 1.000), or length of stay (7.5 days versus 8.3 days; P = 0.360). Postoperative hepatic insufficiency (defined as a postoperative bilirubin level of >7 mg/dl or significant ascites), occurred less frequently after RPS (1.0% versus 8.5%; P = 0.005). Operation type remained an independent determinant of postoperative hepatic insufficiency after controlling for preoperative risk factors (RH: hazard ratio = 9.628, 95% confidence interval 1.295–71.573; P = 0.027). A total of 28 (4.8%) patients died within 90 days; these included 25 (5.2%) patients in the RH group and three (3.0%) in the RPS group ( P = 0.449). Conclusions: Despite similar blood loss and overall morbidity, RPS is associated with less hepatic insufficiency than RH. Right posterior sectorectomy is parenchyma‐sparing and should be strongly considered when it is technically feasible and oncologically sound.